Analysis of Service Quality, Price and Customer Trust on Loyalty at Fritto Chicken on Asia Medan Street - Situmorang, Irvan Rolyesh; Artan, Silvia; Artan, Silvina; Melyani, Melyani (CNPLUS Publisher, 2024)
The Fritto Chicken is a fast-food franchise located in Medan, known for its specialty in fried chicken. Amidst the rapid growth of the culinary industry and intense competition, the Fritto Chicken branch must strive to maintain customer loyalty. Key factors such as service quality, pricing, and brand trust are essential to evaluate in order to remain competitive and foster customer retention. This research was conducted to explore how service quality, pricing, and customer trust contribute to building loyalty among patrons of the Fritto Chicken branch. A quantitative method with a causal associative approach was employed, gathering data through questionnaires distributed to 100 customers. The study utilized theoretical frameworks surrounding service quality, pricing, and customer trust to assess their positive and significant influence on customer loyalty.